FYI (online): supporting the student learning journey from near and far. (1st January 2012) - Noble, Karen; Henderson, Robyn; Pauley, Ron
Across universities, a plethora of approaches has been designed to initiate beginning students into higher education. This paper describes a particular approach, the FYI programme, which operates in the faculty of education of an Australian university. Using a learning circle approach, the programme privileges relationships and social support. Importantly, this programme operates in the spaces between courses and brings first year students together, regardless of the courses they are enrolled in. The on-campus programme offers evidence of tangible impacts upon the quality of participants' interactions, relationships and friendships and their commitment to complete their undergraduate student learning journey. Following three years of on-campus delivery, the programme is now being piloted in the online environment to support students enrolled in blended and fully-online study modes. The initial perspectives of academic and support staff as well as students inform initial critical reflection on the programme's design and delivery. The article concludes that, regardless of access and mode of study, high quality interactions with peers and academic staff in an informal context is vital to the building of enhanced capacity for higher education students.